Anti-Tumor Necrosis Factor Receptor 2 Antibody Combined With Anti-PD-L1 Therapy Exerts Robust Antitumor Effects in Breast Cancer - Qiang Fu (Frontiers Media S.A., 2021)
Breast cancer is a leading type of malignant tumor in women; however, the immunotherapy in breast cancer is still underappreciated. In this study, we demonstrated that tumor necrosis factor receptor 2 (TNFR2) is highly expressed in both breast tumor tissue and tumor-infiltrating immunosuppressive CD4+Foxp3+ regulatory T cells (Tregs). We found that TNFR2 antagonistic antibody reduced Foxp3 expression and the proliferation of Tregs and impaired the inhibitory effect of Tregs on CD4+CD25– effector T (Teff) cells in a dose-dependent manner. The treatment of anti-TNFR2 antibody not only inhibited the proliferation of breast tumor cells in vitro but also suppressed the tumorigenesis of murine mammary carcinoma 4T1 cells in vivo. Mice recovered from tumor growth also developed 4T1-specific immunity. Furthermore, we demonstrated that anti-TNFR2 antibody in combination with anti-PD-L1 exhibited augmented antitumor effects than monotherapy. Anti-TNFR2 treatment also tended to increase the expression of proinflammatory cytokines in tumor tissues. In conclusion, our study suggests that TNFR2 antagonist could potentially offer a clinical benefit as a single agent or in combination with immune checkpoint blockade treatment for breast cancer immunotherapy.